Islamic architecture, the problem of naming - Nahed Taha Al-Qaymaqji; Ahmed Abdul Wahid Dhnoon; Maha Nahed Al-Qaymaqji (The Scientific Journal of Cihan University– Sulaimaniya, 2020)
The historical emergence of the term (Islamic Architecture) has played an important role in the use, to consolidate the belief in linking between the architectural achievements of the Muslims with the religion of Islam. It raises several problematic issues and a very vital question about, what is the relation between Islam and architecture. The research attempts to reach the semantic depth of this term and discusses the problems it raises in order to judge its credibility in expressing the cultural heritage of the peoples that condemned Islamic Religion and its potential to create a common understanding among its users so that it does not fall into the trap of narrow regionalism and limited ideology and gives a comprehensive description of its implications. Adopting an inductive methodology, the research initially asked several questions related to the term (Islamic Architecture) and to answer, it discussed the problems raised by that term, which relate to the form, content, and identity, in order to reach the accurate significance of the use of the term and thus determine its efficiency in the overall meaning description.